2019
DOI: 10.3390/ijms20153778
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian Expression of Adipokines in Polycystic Ovary Syndrome: A Role for Chemerin, Omentin, and Apelin in Follicular Growth Arrest and Ovulatory Dysfunction?

Abstract: Adipokines are a potential link between reproduction and energy metabolism and could partly explain some infertilities related to some pathophysiology, such as polycystic ovary syndrome (PCOS). However, adipokines were predominantly assessed in blood samples, while very little is known concerning their variations in follicular fluid (FF) and ovarian granulosa cells (GCs) of PCOS women. Thus, the objectives of our study were to investigate adiponectin, chemerin, resistin, visfatin, omentin, and apelin ovarian e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
48
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(51 citation statements)
references
References 94 publications
3
48
0
Order By: Relevance
“…Chemerin was first identified as a novel retinoid-responsive gene in psoriatic skin lesions [ 80 ]. In addition to skin, chemerin is widely expressed throughout the human body and is mainly produced by the liver, WAT, and placenta [ 70 ] but is also found in the brain, spinal cord, spleen, lymph node, thymus, stomach, small intestine, colon, kidneys, testis, ovary, pituitary, lungs, heart, skeletal muscle, pancreas, arteries, cartilage, or gingival tissues [ 74 , 81 , 82 , 83 , 84 , 85 , 86 ]. The adipose tissue production of chemerin and CMKLR1 receptor in humans and mice was described in 2007, when chemerin came to be considered a new adipokine [ 87 ].…”
Section: Role Of Some Adipokines In Inflammatory Processes Associamentioning
confidence: 99%
“…Chemerin was first identified as a novel retinoid-responsive gene in psoriatic skin lesions [ 80 ]. In addition to skin, chemerin is widely expressed throughout the human body and is mainly produced by the liver, WAT, and placenta [ 70 ] but is also found in the brain, spinal cord, spleen, lymph node, thymus, stomach, small intestine, colon, kidneys, testis, ovary, pituitary, lungs, heart, skeletal muscle, pancreas, arteries, cartilage, or gingival tissues [ 74 , 81 , 82 , 83 , 84 , 85 , 86 ]. The adipose tissue production of chemerin and CMKLR1 receptor in humans and mice was described in 2007, when chemerin came to be considered a new adipokine [ 87 ].…”
Section: Role Of Some Adipokines In Inflammatory Processes Associamentioning
confidence: 99%
“…The presence of a correlation between serum apelin levels and insulin resistance in PCOS is still controversial (22). Chang et al (23) evaluated both obese and non-obese cases in their study and found that the level of apelin in PCOS patients was lower than the control group.…”
Section: Discussionmentioning
confidence: 99%
“…Hypothetically, APLN controls several aspects of ovarian function in PCOS, underpinned by its role in steroid hormone regulation and insulin resistance. Firstly, the concentration of APLN and its receptors were detected to be significantly increased in PCOS patients with a positive correlation between follicle count and APLN levels (Bongrani et al, 2019). This process could be explained by a steroid hormone disturbance effect of APLN in HPG axis.…”
Section: Regulation Of Apln In Pcosmentioning
confidence: 92%